Natural Products for Cancer Therapy: A Review of Their Mechanism of Actions and Toxicity in the Past Decade - Yasir Osman Ali Abdalla; Bavani Subramaniam; Shaik Nyamathulla; Noorasyikin Shamsuddin; Norhafiza M. Arshad; Kein Seong Mun; Khalijah Awang; Noor Hasima Nagoor (Journal of Tropical Medicine)
The ethnopharmacological information gathered over many centuries and the presence of diverse metabolites have made the medicinal plants as the prime source of drugs. Despite the positive attributes of natural products, there are many questions pertaining to their mechanism of actions and molecular targets that impede their development as therapeutic agents. One of the major challenges in cancer research is the toxicity exerted by investigational agents towards the host. An understanding of their molecular targets, underlying mechanisms can reveal their anticancer efficacy, help in optimal therapeutic dose selection, to mitigate their side effects and toxicity towards the host. The purpose of this review is to collate details on natural products that are recently been investigated extensively in the past decade for their anticancer potential. Besides, critical analysis of their molecular targets and underlying mechanisms on multiple cancer cell lines, an in-depth probe of their toxicological screening on rodent models is outlined as well to observe the prevalence of their toxicity towards host. This review can provide valuable insights for researchers in developing methods, strategies during preclinical and clinical evaluation of anticancer candidates.